(untitled) (Bangladesh Journal of Child Health, 2013)
Introduction: Neonatal hyperbilirubinemia is a cause of major concern for the parents as well as the pediatricians due to chance of neurotoxicity. Early prediction of development of significant hyperbilirubinemia can reduce anxiety and duration of hospital stay. Objective: To find out the risk of development of significant hyperbilirubinemia among preterm newborn within first seven days of life. Methodology: This prospective study was carried out in Dhaka Shishu Hospital during the period of January to June, 2007. One hundred & eleven preterm newborns of 30-37 weeks gestational age were enrolled in first day of their life and their serum total and indirect bilirubin were estimated on the 1st, 2nd, 5th & 7th day. Neonates with evidence of hemolysis, direct hyperbilirubinemia, sepsis & major congenital malformation were excluded. Their 1st and 2nd day serum total bilirubin values were analyzed statistically at different cut off points from which significant hyperbilirubinemia can develop on 5th & 7th day of life. Results: The study included 111 premature neonates of 30-37 weeks gestation who were enrolled on first day of their life. Their mean gestational age was 33.7(±2) weeks and mean birth weight was 1754(±341) gm. Of them, 38 (34%) neonates developed significant hyperbilirubinemia within first seven days of life. Among the study population, 40 (36%) neonates had serum total bilirubin value of <2 mg/dL on first day of life. None of them developed significant hyperbilirubinemia (100% negative predictive value). Again 65 (58.5%) neonates had serum total bilirubin value of <5 mg/dL on second day of life. Among them only 7.6% developed significant hyperbilirubinemia (92.3% negative predictive value). Conclusion: The first and second day serum total bilirubin values can predict subsequent hyperbilirubinemia within seven days of life. First day serum total bilirubin value of 2 mg/dL can be taken as a safe limit from which chance of significant hyperbilirubinemia is less. DOI: http://dx.doi.org/10.3329/bjch.v37i2.17265 BANGLADESH J CHILD HEALTH 2013; VOL 37 (2) : 85-89